Effects of salinity on growth, antioxidant contents and proximate compositions of Sabah snake grass (Clinacanthus nutans (Burm. F.) Lindau) - Uddin, Md Kamal; Shamsuzzaman, S. M.; Lo, Qiau Zi; Medom, Mohd Selamat; Hasan, Mahmudul (Bangladesh Botanical Society, 2017)
This study was carried out to determine the effect of salinity on growth, antioxidant contents and proximate compositions of Sabah snake grass (Clinacanthus nutans (Burm. f.) Lindau). Six salinity levels were used, namely 0 (control), 4, 8, 12, 16 and 20 dS/m. Highest salinity level, 20 dS/m, significantly increased the phenolic content (1.95 mg GAE/g), flavonoids content (3.84 mg QE/g), and proximate compositions such as ash content (19.83%), crude protein content (16.43%), crude fat content (18.45%) and crude fiber content (10.73%) of C. nutans although the plant growth and leaf relative water content were reduced. Therefore, salt-stressed C. nutans can be considered as excellent sources of antioxidant contents and protein for human consumption.